Analisis Faktor-Faktor Penyebab Rendahnya Motivasi Belajar Siswa pada Mata Pelajaran Bahasa Indonesia di Sekolah Dasar 106811 Bandar Setia - Anjeli Mutiara Sella Simanjuntak; Khairunnisa Nasution; Susmitha Marina Angel; Mei Vina Estetika Br Sembiring; Anastasia Desmeria Br Ginting; Sofia Maharaja; Riski Margaretha Nadeak; Rehan Shafira; Sri Rahayu (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
Student learning motivation is an important component in the educational process that influences student success, especially in Indonesian language subjects in elementary schools. This research aims to analyze the factors that cause students' low learning motivation towards Indonesian language subjects. This research uses a qualitative approach using interviews and observations in class V of SD Negeri 106811 Bandar Setia. The research results show several factors that influence students' low learning motivation, such as personal interest, perception of subjects, teaching methods, learning environment and availability of learning resources. This research provides practical recommendations for educators and stakeholders to increase student learning motivation in Indonesian language subjects in elementary schools.